ENHANCING GOVERNANCE THROUGH SHARIA AUDITS: A CASE STUDY OF SARI ASIH SHARIA-CERTIFIED HOSPITAL IN INDONESIA: MENINGKATKAN TATA KELOLA MELALUI AUDIT SYARIAH: STUDI KASUS RUMAH SAKIT BERSERTIFIKASI SYARIAH SARI ASIH DI INDONESIA - Muhammad Yusuf Fakhri; Barokah Wibisono; Ahmad Suhaimi; Ahmad Khoirudin (Universitas Wahid Hasyim Semarang, 2025)
The high Muslim population today has resulted in the need for Sharia health services increasing in line with the concept of halal lifestyle and the development of the halal industry in Indonesia. The urgency of sharia-certified health services that have been inaugurated by the Indonesian Council of Islamic Health Efforts (MUKISI) causes health institutions to undergo a Sharia audit process in their governance to ensure the implementation of Sharia values that prioritize health, hygiene, comfort and Sharia compliance. This study aims to determine the role of Sharia audit in the governance of Sari Asih Hospital. The research method used is a literature study sourced from literature review such as books, journals, websites, the Qur'an, fatwas, and legislation. The results showed that the Sharia audit on the governance of Sari Asih Hospital uses KNKG principles consisting of Transparency, Accountability, Responsibility, Independence, and Fairness or equality. Sharia audit at Sari Asih Hospital is considered not optimal because there are still some irregularities that occur in its governance.